Isolation, Molecular Cloning, and Expression of yyxA Serine Protease Gene Extracted from Bacillus licheniformis in Escherichia coli - Zahra Aghaei Jeshvaghani; Ramin Hoseini (مجله بیوتکنولوژی کشاورزی, 2021)
Objective Proteases are among the most important industrial enzymes. Microbial proteases, especially from Bacillus sp., are most widely exploited industrially. The aim of this study was isolation, cloning, sequencing, expression, and bioinformatics study of yyxA serine protease gene extracted from Bacillus licheniformis.